THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, DISCIPLINE, PRODUCTIVITY ON EMPLOYEE PERFORMANCE - Fathan Arif (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
There are many ways that can be done to improve performance, including presenting a visionary leader, clear discipline rules, and productivity. This research will specifically measure how the role of the leader, discipline rules, and current productivity levels on performance. Thus, a picture of the situation is obtained which is useful for employee development in the future. The scientific method used is quantitative and regression analysis. The research sample was the employees of Hotel Kemang. The results of the study confirm that the increase in performance is strongly influenced by many factors, including leadership, discipline, and work productivity levels. Furthermore, the productivity variable is one of the many factors that indicate good employee performance. Therefore, companies can pay more attention to this matter